OPTIMALISASI STRATEGI DIGITAL MARKETING BAGI UMKM DALAM MENINGKATKAN POTENSI EKONOMI DESA - Ramadhan, Tri Sugiarti; Primanto, Alfian Budi; Normaladewi, Andi (Universitas Mataram, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in national economic growth and improving the welfare of the surrounding community. However, MSMEs are certainly not free from obstacles, especially for small-scale MSMEs, on average there are obstacles in marketing and distributing products or services such as those that occur in MSMEs in Kedung Banteng Village, Sumbermanjingwetan District. There are several types of MSMEs such as Banana Chips, Angkring Anyam Tas, catering, etc. Through the Community Service Study Program (SKM), it is one form of student role in developing MSMEs so that local products are better known and in demand by the community, and increase the income of local village MSMEs. Efforts made through the SKM program are: how to improve the quality of MSME competitiveness in Kedungbanteng Village, how MSMEs in Kedungbanteng Village can learn about the use of digital marketing, branding, and basic bookkeeping. Therefore, in the CSS program there are two activities, namely the socialization of digital marketing and financial technology; training on the use of digital media for promotion and sales such as e-commerce Facebook, WhatsApp Business, LinkThree, and Shopee; as well as the creation of logos and content that are in accordance with trends that aim to increase the potential of MSMEs in Kedungbanteng Village, Sumbermanjingwetan District, Malang Regency.